2014
DOI: 10.1088/1674-1056/23/10/107303
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of improving forward and reverse blocking voltages in AlGaN/GaN HEMTs by using Schottky drain

Abstract: Mechanism of improving forward and reverse blocking voltages inAlGaN/GaN HEMTs by using Schottky drain * Zhao Sheng-Lei(赵胜雷) a) , Mi Min-Han(宓珉瀚) a) , Hou Bin(侯 斌) b) , Luo Jun(罗 俊) a) , Wang Yi(王 毅) a) , Dai Yang(戴 杨) a) , Zhang Jin-Cheng(张进成) a) , Ma Xiao-Hua(马晓华) a)b) , and Hao Yue(郝 跃) a) † a)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…G ALLIUM nitride-based high electron mobility transistors (HEMT's) exhibit superior performance in terms of wider bandgap (varying from 3.4eV to 6.2eV for AlGaN), high-power, high-temperature, high-voltage, and high-frequency applications [1][2][3] due to their sustainable properties such as high mobility (>1500cm 2 /V.s) [4], [5], high saturation velocity, high-thermal conductivity, high breakdown field (∼10 6 Vcm -1 ), and high two-dimensional electron gas (2-DEG) sheet charge density (10 13 cm -2 ) at the hetero-interface [6][7][8] . But, the major drawbacks of HEMT based devices are higher gate leakage current [9] and drain current collapse during operation at higher frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…G ALLIUM nitride-based high electron mobility transistors (HEMT's) exhibit superior performance in terms of wider bandgap (varying from 3.4eV to 6.2eV for AlGaN), high-power, high-temperature, high-voltage, and high-frequency applications [1][2][3] due to their sustainable properties such as high mobility (>1500cm 2 /V.s) [4], [5], high saturation velocity, high-thermal conductivity, high breakdown field (∼10 6 Vcm -1 ), and high two-dimensional electron gas (2-DEG) sheet charge density (10 13 cm -2 ) at the hetero-interface [6][7][8] . But, the major drawbacks of HEMT based devices are higher gate leakage current [9] and drain current collapse during operation at higher frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, a single integrated bidirectional blocking device, instead of using a discrete transistor in series with a discrete Schottky barrier diode (SBD), could achieve high blocking voltages under both forward and reverse drain biases, which can obviously reduce the parasitic elements and further improve the power conversion efficiency. Nowadays, the reverse blocking capability of GaN-based power devices are realized by integrating a SBD at drain electrode [12][13][14][15][16][17][18]. It is vital to reduce the forward turn-on voltage (V on ) caused by SBD because the lower V on is helpful to decrease the on-state power loss and thus to improve the overall power efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…A reverse blocking device or circuit must be added to the switching device to achieve unidirectional characteristics, which enlarges the chip size and increases the manufacturing cost. Some studies have reported the unidirectional operation of GaN devices without adding extra components [ 14 , 15 , 16 , 17 , 18 ]. In this study, we proposed a unidirectional switching device that is based on a normally-off p-GaN gate AlGaN/GaN HFET in which a drain electrode consisted of a rectifying gating electrode and an ohmic electrode.…”
Section: Introductionmentioning
confidence: 99%